Yield stress for zeolite-cement grouted sand. (30th June 2020) - Jafarpour, Peyman; Ziaie Moayed, Reza; Kordnaeij, Afshin
Highlights: The axial yield strain in all zeolite-cement grouted specimens is less than 1%. The q ( y ) and c′y increase by increasing the Z in the grouted specimens up to 30%. An increase of more than 30% in Z leads to a decrease in q ( y ) and c′y. With increasing Z content, the φ′y increases with a slight slope. Abstract: Permeation grouting with cementitious materials is a widely used soil behavior improvement technique. Since the Portland cement production leads to environmental pollution and is also an energy-intensive process, replacing a part of the cement with cheaper and more environmentally friendly materials, such as zeolite, is very important. In the present study, a series of consolidated undrained triaxial tests were carried out on zeolite-cement grouted sand specimens to investigate the effect of cementation on the yield stress ( q ( y ) ) through shear loading. The results showed that the axial yield strain ( ε ( y ) ) in all zeolite-cement grouted sand specimens is less than 1%. Beyond the yield point ( YP ), a sudden increase in the strain occurs, and the stress–strain curve continues with a slight gradient. The effect of cementitious bonds is significant up to the YP and then gradually decreases. The effective stress path ( ESP ) of the grouted specimens rises approximately vertically up to the YP . Beyond the YP, the abrupt change of the curvature occurs and the ESP turns to the right. The q ( y ) and cohesion corresponding to the YP ( c′y ) increase by increasing the amount of cement replacement with zeolite ( Z ) in the grouted specimens up to 30%. An increase of more than 30% in Z leads to a decrease in q ( y ) and c′y . Therefore, the optimum Z to achieve the maximum q ( y ) and c′y is 30%. With increasing Z content, the effective internal friction angle corresponding to yield ( φ′y ) always increases with a slight slope.